Gas tamponade combined with laser photocoagulation therapy for congenital optic disc pit maculopathy - Lei, L (Eye (Lond), 2015)
PURPOSE: To evaluate the long-term clinical efficacy and safety of gas tamponade combined with laser photocoagulation for optic disc pit maculopathy. METHODS: Seven consecutive patients with unilateral maculopathy associated with optic disc pit and one patient with bilateral optic disc pit maculopathy were given octafluoropropane (C(3)F(8)) tamponade combined with focal laser photocoagulation treatment. Patients were followed up for 21–62 months after treatment. Main outcomes were determined by optical coherence tomography (OCT) and best-corrected visual acuity (BCVA). RESULTS: Treatment with C(3)F(8) tamponade followed by laser photocoagulation in ODP maculopathy patients resulted in resolution of sub-retinal and/or intra-retinal fluid in six out of eight patients. The remaining two patients had significant reduction in fluid, as determined by OCT, and funduscopy, as well as an improvement in anatomical architecture. Visual acuity improved obviously in seven eyes and remained stable in two eyes. Central visual field loss after photocoagulation was not clinically appreciable by visual field examination. No post-operative complications of maculopathy occurred during the follow-up period. CONCLUSIONS: Although repeated treatment was needed in some patients, C(3)F(8) tamponade combined with laser photocoagulation is still a simple, effective, minimally invasive, and economic therapy for optic disc pit maculopathy.